(untitled) (Nepal Agriculture Research Journal, 2009)
An experiment was conducted on Rhodic Ustochrept soil in Central Hill of Nepal growing wheat-mungbean-rice in rotation. Grain yields as affected by 28 t ha-1 a of town compost were compared with the same amount of farmyard manure and N:P:K (120:60:40). NPK produced significantly higher wheat grain (3897 t ha-1). Other yield results were at par with one another. NPK produced lowest mungbean yield. After growing second crop fertility seems to be exhausted thus rice yield indicated no notable residual fertilising effect. FYM and town compost left noteworthy amounts of P, Ca, Mg and K even after rice harvest. Key words: Organic manure; plant nutrients; sustainability DOI: 10.3126/narj.v7i0.1868 Nepal Agriculture Research Journal Vol.7 2006 pp.49-53